2019
DOI: 10.3389/fsufs.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

Digestate Biofertilizers Support Similar or Higher Tomato Yields and Quality Than Mineral Fertilizer in a Subsurface Drip Fertigation System

Abstract: This study investigated the effects of applying anaerobically digested food waste and dairy manure-derived biofertilizers to processing tomatoes. The biofertilizers were produced from a pilot scale system consisting of coarse solid separation and ultrafiltration (5,000 Da) with a capacity of approximately 3.8 m 3 •d −1. The coarse solids had particle size >53 µm and were not used for drip fertigation. The liquid concentrate and permeate from the system were both delivered to tomato plants through a subsurface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 59 publications
2
30
0
3
Order By: Relevance
“…Cavigelli et al [18] reported that nitrogen availability and weed control are the two main factors influencing crop yield in the OFS. Particularly, nitrogen is one of the main essential nutrients for tomato growth [19]. Scholberg et al [20] reported that nitrogen deficiency can reduce tomato leaf area index, biomass production and fruit yield within a range from 60% to 70%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavigelli et al [18] reported that nitrogen availability and weed control are the two main factors influencing crop yield in the OFS. Particularly, nitrogen is one of the main essential nutrients for tomato growth [19]. Scholberg et al [20] reported that nitrogen deficiency can reduce tomato leaf area index, biomass production and fruit yield within a range from 60% to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Other researches highlighted improving in quality and yield of digestate-fertilized crops. In fact, Barzee et al [19] reported that tomatoes fertilized with digestate had higher soluble solids contents then synthetically fertilized one, and Šimon et al [26] reported increases in grain yield in Triticum aestivum L. to respect the untreated control.…”
Section: Introductionmentioning
confidence: 99%
“…This approach could also be applied under field conditions where targeted management of soil community composition could be promoted around the plant root system with the application of digestates through drip fertigation systems. Barzee et al (2019) investigated the feasibility of drip fertigation for the application of digestate biofertilizers (rich in N, P, K as well as Cu, Ni, Mg, and Zn) to tomato crops in farm-scale cultivation experiments. Their results demonstrated that digestate biofertilizers could also be effectively delivered to the tomato plants through a subsurface drip irrigation system, with increased crop yields.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in other cases, controlled management of liquid digestates through drip irrigation systems in open field or protected citrus orchards could be implemented to enhance native soil beneficial microbial communities. Furthermore, improvement of indoor citrus nursery production could come from adopting zero run-off irrigation systems where 100% of irrigation/fertigation water is recycled and reused however, these are understudied areas (Bailey and Lazarovits, 2003;Bonilla et al, 2012;Cao et al, 2016;Ciancio et al, 2016;Barzee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Option 1 the process is the same as in Option 2, only the treated digestate is used as a fertilizer on agricultural soils due to newly formed materials (magnesium ammonium phosphate hexahydrate and calcium phosphate dihydrate). It is also important to mention that after separation to a solid and liquid fraction in these processes, digestate liquid fraction can be used on agricultural soils as a fertigation liquid, which helps improve the characteristics of the soil [31,32].…”
Section: Options For Digestate Treatmentmentioning
confidence: 99%